Welcome :: Homework Help and Answers :: Mathskey.com
Welcome to Mathskey.com Question & Answers Community. Ask any math/science homework question and receive answers from other members of the community.

13,435 questions

17,804 answers

1,438 comments

97,189 users

Find the remaining factors for x4 - 10x3 + 35x2 - 50x + 24 if two factors are x - 1, and x - 3.

0 votes
synthetic division
asked Aug 24, 2014 in PRECALCULUS by anonymous

3 Answers

0 votes

The factors are (x-1)(x-3)

(x-1)(x-3) =x² -4x+3

f(x) = x4 - 10x3 + 35x2 -50x+24.

x² -4x+3)x4 - 10x3 + 35x2 -50x+24 (-6x+8

            (-)       x4    - 4x3 + 3x2

            ---------------------------------

                             -6x3 +32x2 -50x+24

                     (-)      -6x3 +24x2 -18x

                  ---------------------------------

                                          8x2 -32x+24

                     (-)                 8x2-32x+24

                     ---------------------------------

                                       0

         

f(x) = x4 - 10x3 + 35x2 -50x+24 =(x² -4x+3)(x²-6x+8)

                                                    =(x-1)(x-3)(x²-6x+8)

Find the factors of (x²-6x+8)

(x²-6x+8) =(x²-4x-2x+8)

                       =x(x-4)-2(x-4)

                       =(x-2)(x-4)

Remaining factors are (x-2) and (x-4)         

answered Aug 24, 2014 by bradely Mentor
reshown Aug 25, 2014 by bradely
i dont get it.
dont understand,can you plz explain.
where did the x²-6x+8 come from?
please check modified solution
0 votes

First find the reduced expression when (x-1) is factor.

Step 1 : Write the terms of the dividend so that the degrees of the terms are in descending order. Then write just the coefficients as shown at the right.

Step 2 : Write the constant r of the divisor (x - r ) to the left. In this case, r = 1. Bring the first coefficient, 1, down.

image

Step 3 : Multiply the first coefficient by r : 1(1) = 1. Write the product under the second coefficient, -10 and add : -10 + 1 = -9.

image

 

Step 4 : Multiply the first coefficient by r : 1(-9) = -9. Write the product under the second coefficient, 35 and add : 35 +( -9) = 26.

image

Step 5 : Multiply the first coefficient by r : 1(26) = 26. Write the product under the second coefficient, -50 and add :  -50 +(26) = -24.

image

Step 6 : Multiply the first coefficient by r : 1(-24) =- 24. Write the product under the second coefficient, 24 and add :  24 +(-24) = 0.

image

So reduced expression is x³- 9x² +26x - 24

Second factor is (x-3).

Next find the reduced form when  (x-3) is factor.

answered Aug 25, 2014 by bradely Mentor
0 votes

conti.....

Step 1 : Write the terms of the dividend so that the degrees of the terms are in descending order. Then write just the coefficients as shown at the right.

image

Step 2 : Write the constant r of the divisor (x - r ) to the left. In this case, r = 3. Bring the first coefficient, 3, down.

image

Step 3 : Multiply the first coefficient by r : 3(1) = 3. Write the product under the second coefficient, -9 and add : -9 + 3 = -6.

image

 

Step 4 : Multiply the first coefficient by r : 3(-6) = -18. Write the product under the second coefficient, 26 and add : 26 +( -18) = 8.

image

Step 5 : Multiply the first coefficient by r : 3(8) = 24. Write the product under the second coefficient, -24 and add :  -24 +(24) = 0.

image

So reduced expression is x²- 6x+8

Find the factors of (x²-6x+8)

(x²-6x+8) =(x²-4x-2x+8)

                       =x(x-4)-2(x-4)

                       =(x-2)(x-4)

Remaining factors are (x-2) and (x-4)

answered Aug 25, 2014 by bradely Mentor

Related questions

...